Analisis Akademik Inklusi Dan Perkembangan Menangani Siswa ABK Autisme SDN Bojong 1 Pinang Kota Tangerang - Mardiyanto, Muhammad Sodiq; Mahardhika, Gita; Januar, Nur Haliza; Ramadhanti, Marsya Afifa; Rizky, Rafa Fauziyyah; Amanda, Yunita; Ramadhani, Annisa Nurul; Hothimah, Ryani Husnul; Erika, Siti Anisa; Zahra, Zaira Anisa; Habsah, Dinda Anisa; Fadhillah, Septy Nur; Nuraeni, Yeni Nur (Peneliti.net, 2024)
This qualitative case study explores academic inclusion and the development of students with autism at SD Negeri Bojong 1 Pinang, Tangerang City. The study involves various stakeholders, including the school principal, class teachers, inclusion teachers, and students with autism. SD Negeri Bojong Pinang 1 adopts an inclusive approach with specific enrollment criteria for students with autism, fostering collaboration between inclusion and class teachers. Challenges include addressing the independent learning tendencies of students with autism. Effective teaching strategies and individual-focused approaches are pivotal for establishing an inclusive and supportive educational environment. The discussion encompasses academic inclusion management, emphasizing facility utilization and the pivotal role of dedicated inclusion teachers. Autism characteristics, classified based on developmental stages and behavioral symptoms, are delineated. The study concludes that SD Negeri Bojong 1 Pinang serves as an exemplar of an inclusive educational institution with collaborative teaching approaches, contributing valuable insights into educating children with autism within an inclusive school context.